(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The ocean is both a precious resource for coastal communities and a vast source of largely untapped renewable energy that can help combat climate change. This presents a unique opportunity for wave energy converters (WEC) to provide both utility-scale and small-scale electricity for resilient, energy-efficient communities that can better withstand the effects of climate change. Designing a WEC is not straightforward as the ocean supports a wide range of uses and the highly energetic environment can threaten survival. This requires WEC designers to deconflict their use area and select deployment locations that minimize risk. Subsurface WEC designs provide a potential solution for these challenges as their deployment depth can mitigate area-use conflicts with other ocean users. A fully submerged WEC also has increased survivability due to being in a less energetic environment and at a depth that they are less likely to collide with ocean vessels. However, a submerged WEC may also suffer from the less energetic environment as it decreases the amount of electricity the WEC can generate. These tradeoffs make it unclear when subsurface WECs are beneficial to deploy. There is little research to date that offers comprehensive understanding of this field of WECs in regard to their capabilities or constraints. This paper presents a method for characterizing and understanding the functions of WEC archetypes by leveraging functional decomposition to examine high level overlaps between archetypes. Functional decomposition is a well-established engineering design method for breaking down complex systems into constituent parts to track flows of energy, information, and materials. The method enables engineers understand how each component contributes to the overall functionality of the system and enables us to analyze functional performance overlaps between WEC archetypes. We apply this method to submerged WECs and present an analysis of the high level functions. The findings of this case study shed light on the functional uniqueness of submerged WEC archetypes and can be used to guide future development in subsurface WEC technology. Better identifying functional overlaps between WEC archetypes will help researchers and developers generate effective designs that build resilient coastal communities.